(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2023)
The mediating role of exosome-mediated signalling in the inflammatory response is significant. Exosomes transport a wide variety of biomacromolecules, such as proteins, lipids, coding and non-coding RNAs, and a variety of lengths of RNA, to the cells they infect in order to carry out their biological or pathological activities. Therapeutic effects may be conferred by attenuating or boosting the immune response via exosomes released by antigen-presenting cells. In order to modify T cell responses specific to antigens, exosomes are essential for transporting and displaying functional major histocompatibility peptide complexes. Dendritic cell (DC) exosomes have immunostimulatory capabilities and have been investigated for use in cancer treatment due to their ability to stimulate T and B cells. In animal models of several inflammatory diseases, exosomes produced by macrophages and DCs have immunosuppressive characteristics that alleviate inflammation. Research on exosomes produced by dendritic cells (DCs) and macrophages (macrophages) is the primary emphasis of this review, which aims to shed light on the protective function of exosomes in reducing inflammation and enhancing the immune response.